2005
DOI: 10.1038/sj.npp.1300983
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between In Vivo Occupancy and Functional Antagonism of Dopamine D2 Receptors: Comparing Aripiprazole to Other Antipsychotics in Animal Models

Abstract: The novel antipsychotic aripiprazole requires high (490%) striatal D 2 receptor occupancy (D 2 RO) to be clinically active, but despite its high D 2 RO it does not show extrapyramidal symptoms. While most antipsychotics are active at nearly 65% D 2 RO, they show motor side effects when D 2 RO exceeds 80%. We investigated this discrepancy between D 2 RO, 5HT 2 receptor occupancy (5-HT 2 RO) and in vivo functional activity of aripiprazole in comparison to haloperidol (typical) and risperidone (atypical) in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
116
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 43 publications
(57 reference statements)
10
116
1
2
Order By: Relevance
“…The lower affinity to D 2 receptors compared to 5-HT 2 receptors partially explains NDMC's lack of significant occupancy at the D 2 receptors, 1 h after administration. The low D 2 RO of NDMC is consistent with its lack of catalepsy or prolactin elevation, as these measures have been closely linked to D 2 RO for other agents (Wadenberg et al, 2000b;Natesan et al, 2006). In the AIL model, NDMC had the least effects among the established antipsychotics tested.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The lower affinity to D 2 receptors compared to 5-HT 2 receptors partially explains NDMC's lack of significant occupancy at the D 2 receptors, 1 h after administration. The low D 2 RO of NDMC is consistent with its lack of catalepsy or prolactin elevation, as these measures have been closely linked to D 2 RO for other agents (Wadenberg et al, 2000b;Natesan et al, 2006). In the AIL model, NDMC had the least effects among the established antipsychotics tested.…”
Section: Discussionsupporting
confidence: 52%
“…The Fos expression induced by a dose of 60 mg/kg for NDMC does not exceed this threshold and could explain the lack of effect in CAR at early time points. The emergence of catalepsy is correlated with a certain threshold of Fos expression (430 counts) in the dorsolateral striatum among antipsychotic agents (Natesan et al, 2006). In the present study, only haloperidol exceeded this level of Fos expression, and showed catalepsy.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The validity of the dose selection can be evaluated by comparison to doses effective in other rodent models of psychosis, by confirming clinically relevant plasma levels and/or DA D 2 receptor occupancies in vivo in the central nervous system. We selected dose ranges of haloperidol, olanzapine, and risperidone that did not produce behavioral disruption and that have been shown to induce DA D 2 receptor occupancies that correspond to therapeutically effective levels reported previously (Zhang and Bymaster, 1999;Natesan et al, 2006;LTB Brennum, H Lundbeck, unpublished), and induce marked behavioral effects in various animal models of psychosis (for review, see Arnt and Skarsfeldt, 1998). Clozapine has weaker DA D 2 in vivo binding potency, but the selected doses examined were within behaviorally active levels, and further dose increase leads to marked sedation (see Arnt and Skarsfeldt, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Also, at the medium and high doses, both haloperidol and clozapine selectively disrupt avoidance responding-a validated behavioral index of antipsychotic activity (Li et al, 2004). The dose for amphetamine was 1.5 mg/kg, which is the common dose used in the literature (Arnt, 1995;Natesan et al, 2006;Sills et al, 2000).…”
Section: Experiments 1: Effects Of Repeated Haloperidol and Clozapine mentioning
confidence: 99%